PSYCHOLOGICAL PROPERTIES OF THE RICHBAR PERSON IN THE MANAGEMENT - Alimova, Qunduz (Журнал Педагогики и психологии в современном образовании, 2021)
Annotation: The article describes the psychological factors of the organization of the management process, the theoretical historical basis of management science, the socio-psychological characteristics of the leader studied at the level of professional demand, and the specific features of the development of effective management activities of the heads of educational institutions.